Representation of deer riders in Mongolian petroglyphs and their implications (Studia Archaeologica, 2023)
While the domestication of some cervids, such as reindeer (Rangifer tarandus), have had a substantial impact on lifeways and societies on Northeast Asian societies would be accurate, there is limited, if any, archaeological evidence for domestication relationships with other cervids such as the Eurasian red deer (Cervus elaphus). This paper investigates a series of deer riding images from petroglyphs found in Mongolia including some other archaeological evidence with deer imagery. Although these petroglyph images are not irrefutable evidence they demonstrate a potential domesticate relationship between deer and humans that has largely been neglected in archaeological research and one which could extend into the past. As absolute dating of petroglyph images is imprecise for certain periods, with the lengthy rock-art tradition in Mongolia, deer domestication could have occurred, but this requires further archaeological investigation. These images represent a first step in temporally locating the domestication of deer species in the area. On the one hand, these deer riding images could be an abstract representation of ritual meaning as deer play prominent roles in ancient belief and shaman customs in this region. However, we suggest here that it is likely indicative that both ancient red and reindeer riding was occurring in Altai and Khangai mountains of Mongolia either a real transport or intended taming for ritual activity.Хадны зураг дахь буга унаачид юу өгүүлнэ вэТовчлол. Зүүн хойд Азийн бүс нутаг орших эртний нүүдэлчдийн аж амьдрал цаа бугын аж ахуйтай салшгүй нягт холбоотой ч анх хэдий үеэс хаана цаа бугыг гаршуулсан цаашлаад халиун бугыг гаршуулж байсан эсэх асуудал нь судалгааны сонирхолтой сэдэв билээ. Чухам үүнийг нэхэн өгүүлэх археологийн баримт хэрэглэгдэхүүн тун хязгаарлагдмал гэж ойлгож болно. Тэр дундаа халиун бугыг гаршуулж, тээвэрт ашиглаж байсан гэх эртний баримт хэрэглэгдэхүүн одоогоор бараг үгүй билээ. Харин энэ удаад бид Монгол орны хадны зургаас илрүүлсэн буга унасан зургийн судалгаанд анхаарал хандуулж улмаар археологийн бусад баримт дээрх буга унасан, тэргэнд хөллөсөн, нуруу ачсан зургуудтай харьцуулан үзэж, хэлэлцүүлэг өрнүүлэхийг зорив. Гэвч хадны зургийн он цаг тогтоох хүндрэлтэй байдлаас үүдэн хэлэлцүүлж буй сэдэвт зургийг тодорхой нарийн цаг үед хамруулж авч үзэхэд бэрхшээлтэй ч хүрлийн үеэс эртний улсуудын үе хүртэлх өргөн цар хүрээнд холбогдох боломжтой. Эдгээр буга унаачдын зургийг аливаа нэгэн зан үйл, үлгэр домгийн утга агуулгатай, хийсвэр дүрслэл хэмээн тайлбарлаж болох ч нөгөө талаар цаа болон халиун бугыг аж ахуй болон зан үйлийн аль нэг хэлбэрээр уналгад ашиглаж байсныг тодорхойлох өнөөгийн Монгол улсын нутгаас олдож буй анхдагч баримтууд хэмээн үзэв.Түлхүүр үг. Халиун буга, цаа буга, гаршуулалт, буга унах, хадны зураг